Evaluation of the Amount and Type of Beverages Consumed by University Students - BATAR, NAZLI; ÖZUĞURLU, İREM BERFE; KOÇAK, BETÜL; Hamurcu, Pınar; SEVDİN, SEZEN (Balıkesir Üniversitesi, 2021)
Objective: This study aims to evaluate the effect of beverage consumption amount and type on body composition of the university students. Materials and Methods: A questionnaire form that contains beverage consumption questions was applied to 201 students studying at the Department of Nutrition and Dietetics, Faculty of Health Sciences, Istanbul Kültür University. The research data were evaluated using the SPSS 25th version program. Results: Of students participated in this study, 91.5% were female and 8.5% male. All 201 students who participated in this study were the students of Nutrition and Dietetics Department. The average age of these students was 20.5±2.1 years. Anthropometric measurements of the students were done, and the mean height was 166.1±7.6 cm, body weight was 59.7±11.3 kg, BMI was 21.54±3.1 kg / m², and hip circumference was 93.6±8.9 cm. In the study, significant relationship was found between BMI and beer types (p=0.028), wine (p=0.019), hard drinks (p=0.016), mineral water and soda (p=0.030) consumption amounts. A very weak statistically significant positive correlation was found between the daily sugared tea consumption and the body weight of university students (rs=0.149; p=0.035). It was observed that there was a statistically positive and weakly significant relationship between daily energy drink consumption and the body weight (rs=0.202; p=0.004). A very weak statistically significant positive correlation was found between the daily consumption of energy drinks and the BMI value (rs=0.163; p=0.021). Conclusion: It was concluded that depending on the consumption amount and variety of the beverages, beverage consumption has a relationship with body weight and BMI.
Üniversite Öğrencilerinde İçecek Tüketim Miktarı ve Türünün Değerlendirilmesi
Keywords: Beverage Consumption; Beverage Amount; University Students; Body Weight